2016
DOI: 10.1016/j.ijthermalsci.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

The extended Graetz problem for micro-slit geometries; analytical coupling of rarefaction, axial conduction and viscous dissipation

Abstract: a b s t r a c tIn order to support the recent MEMS and Lab-on-a-chip technologies, we studied heat transport in micro-scale slit channel gas flows. Since the micro convection transport phenomena diverges from conventional macro-scale transport due to rarefaction, axial conduction and viscous heating, an accurate understanding requires a complete coupling of these effects. For such cases, we studied heat transfer in hydrodynamically developed, thermally developing gas flows in micro-slits at various flow condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Brinkman (Br) number is the ratio of viscous heating over heat conduction in the fluid domain which flows along microchannel, and it is used to determine the effect of viscous dissipation on heat transfer mechanism in MCHS. 110 Kalyoncu and Barisik 71 numerically showed that viscous dissipation increases and decreases heat transfer rate for positive and negative Br cases, respectively. However, they indicated that developed Nu number values are the same for both cases.…”
Section: Viscous Dissipationmentioning
confidence: 99%
See 3 more Smart Citations
“…Brinkman (Br) number is the ratio of viscous heating over heat conduction in the fluid domain which flows along microchannel, and it is used to determine the effect of viscous dissipation on heat transfer mechanism in MCHS. 110 Kalyoncu and Barisik 71 numerically showed that viscous dissipation increases and decreases heat transfer rate for positive and negative Br cases, respectively. However, they indicated that developed Nu number values are the same for both cases.…”
Section: Viscous Dissipationmentioning
confidence: 99%
“…99 An increment in Kn number, Pe number, and hydraulic diameter decreases axial heat conduction rate. 71,[100][101][102] In contrast, the effect of axial heat conduction on heat transfer increases as Re number, thermal conductivity, and thickness of the separating wall increase. 96,102 At the entrance region, the presence of axial heat conduction increases heat transfer rate.…”
Section: Axial Heat Conductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though the classical Graetz problem [1] has been known for over a 100 years, a number of recent investigations related to extended versions of the problem can be found in the literature. Among features that are commonly incorporated as extensions to the classical Graetz formulation, one can mention axial heat diffusion [2][3][4][5][6], different velocity profiles [7], conjugate heat transfer within the surrounding walls [8][9][10][11], slip flow effects [5,6], and heating by viscous dissipation [4,[12][13][14]. These recent examples show that, despite the simplicity of the dynamically developed flows that occur in Graetz formulations, there are many current applications for these problems.…”
Section: Introductionmentioning
confidence: 99%